The Role Of Millennial And Gen Z Preachers On Social Media In Promoting Moderate Islamic Views: Implications For Islamic Education In The Digital Era - Rokimin; Sita Husnul Khotimah; Fatmawati; Nunung Khoiriyah; Armawati Arbi; Kalsum Minangsih (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study investigates the pivotal role of Millennial and Gen Z preachers in promoting moderate Islam through social media platforms such as Instagram, YouTube, and TikTok, and examines the consequent implications for Islamic education in the digital era. The primary objectives are to analyze the strategies these young preachers employ to convey inclusive religious messages, to assess the impact of their digital da'wah on youth audiences, and to critically explore the challenges of maintaining theological depth within the attention-driven economy of social media. Methodologically, this research employs a qualitative phenomenological approach. Data were collected through in-depth interviews with 15-20 young preachers and subjected to systematic thematic analysis, complemented by a structured content analysis of their social media posts to examine the practical negotiation of moderate messaging online. The findings reveal that while these preachers successfully utilize engaging, innovative formats to broaden the reach of tolerant Islamic values, their practice is fundamentally reconfigured by the platform's logic. The research critically identifies the emergence of